Solving Elgar’s Enigma - Santa, Charles Richard; Santa, Matthew (Current Musicology, 2010)
On June 19, 1899, Elgar’s opus 36, Variations on a Theme, was introduced to the public for the first time. It was accompanied by an unusual program note: “It is true that I have sketched for their amusement and mine, the idiosyncrasies of fourteen of my friends, not necessarily musicians; but this is a personal matter, and need not have been mentioned publicly. The Variations should stand simply as a “piece” of music. The Enigma I will not explain-its “dark saying” must be left unguessed, and I warn you that the connexion between the Variations and the Theme is often of the slightest texture; further, through and over the whole set [of variations 1 another and larger theme “goes” but is not played … So the principal Theme never appears, even as in some late dramas-e.g., Maeterlinck’s “L’Intruse” and “Les sept Princesses” -the chief character is never on the stage. (Burley and Carruthers 1972:119)” After this premier Elgar give hints about the piece’s “Enigma;’ but he never gave the solution outright and took the secret to his grave. Since that time scholars, music lovers, and cryptologists have been trying to solve the Enigma. Because the solution has not been discovered in spite of over 108 years of searching, many people have assumed that it would never be found. In fact, some have speculated that there is no solution, and that the promise of an Enigma was Elgar’s rather shrewd way of garnering publicity for the piece. Others have even argued that the larger Enigma was a joke or a hoax; that Elgar never had any Enigma but instead tricked people to search in vain (Rushton 1999:64). Elgar refused to validate any solution offered during his lifetime, and therefore no solution can ever be proven beyond the shadow of a doubt. However, the composer offered a series of hints that provide a rubric for evaluating the plausibility of various solutions.